Effect of gravity field and moving internal heat source on a 2-D problem of thermoelastic fiber-reinforced medium: Comparison of different theories. Issue 9 (3rd May 2019) - Othman, Mohamed I. A.; Said, Samia M.
ABSTRACT: A new fiber-reinforced model has been constructed by taking into account the deformation of a generalized thermoelastic medium with internal heat source. A general model of the equations of the formulation in the context of the Lord–Shulman theory that includes one relaxation time and Green–Lindsay theory with two relaxation times, as well as the classical dynamical coupled theory, is applied to study the influence of gravity and reinforcement on the total deformation of a thermoelastic medium. The normal mode analysis is used to obtain the exact expressions for the physical quantities. The variations of the considered variables with the horizontal distance are illustrated graphically. Comparisons are made with the results in the three theories in the presence and absence of reinforcement, gravity, and moving internal heat source.